On one-dimensional Leibniz central extension of a filiform lie algebra. - Sattarovich, Rakhimov Isamiddin; Hassan, Munther A. (Cambridge University Press (CUP), 2011)
The paper deals with the classification of Leibniz central extensions of a filiform Lie algebra. We choose a basis with respect to which the multiplication table has a simple form. In low-dimensional cases isomorphism classes of the central extensions are given. In the case of parametric families of orbits, invariant functions (orbit functions) are provided.